The copious capabilities of non-coding RNAs in cancer regulation, diagnosis and treatment - Aideen McCabe; Oza Zaheed; Magdalina Derlipanska; George Merrin; Kellie Dean (Cancer Treatment and Research Communications, 2023)
Globally, cancer is one of the leading causes of mortality, accounting for 10 million deaths per year. Non-coding RNAs (ncRNAs) play integral and diverse roles in cancer, possessing the ability to both promote oncogenesis and impede tumor formation. This review discusses the various roles of microRNAs, transfer RNA-derived small RNAs, long non-coding RNAs and lncRNA-derived microproteins in cancer progression and prevention. We highlight the diagnostic and therapeutic potential of these ncRNAs, with a particular focus on detection in liquid biopsies and targeting of ncRNAs with small inhibitory molecules. Ultimately, the biological functions of cancer-associated ncRNAs, as well as the development of ncRNA-based technologies, are compelling areas for further research, holding the possibility of revolutionizing cancer treatment and diagnosis.